Restauración de áreas alteradas de manglar con Rhizophora mangle en la Costa de Chiapas - Reyes Chargoy, Miguel Angel; Tovilla Hernández, Cristian (Instituto de Ecología, A.C., 2016)
The rehabilitation of an area of 2.0 ha of mangrove in the Cabildo and Pozuelos lagoons in the municipality of Tapachula, Chiapas, Mexico, was performed. The restoration involved direct seeding of propagules and seedlings of Rhizophora mangle. In Cabildo, 19 345 hypocotyls were planted between June and August. Later, in September, 3 019 propagules were planted in Pozuelos. After 240 days, seedling height was >61.5 cm and 65.0 cm at the two sites. At the end of the experiment, a total of 15 709 plants had survived from both lagoons. The highest mortality (61.2%) was registered in Cabildo lagoon during February-April, when the site completely dried up. In contrast, in Pozuelos, a permanent flood resulted in high initial survival (98.5%), and the tides fixed many of the propagules thus increasing the number of germinating plants. Up to 550 propagules germinated in a tree nursery. After 120 days, the plants were transported to the field and planted. The mortality of these plants was less than 5% and they grew to a height of 71.77 cm.